Presence of two distinct regions in the coiled-coil structure of the streptococcal Pep M5 protein: relationship to mammalian coiled-coil proteins and implications to its biological properties. - Manjula, B N (1985)
The complete amino acid sequence of Pep M5, a biologically active 197-residue fragment comprising nearly half of the group A streptococcal M5 protein, has structural features characteristic of an alpha-helical coiled-coil protein. Fourier analyses of the nonpolar residues show strong periodicities based on repeats of 7 residues (7/2 and 7/3). Except for the nonhelical NH2-terminal 12-residue segment, the 7-residue periodicity in the distribution of nonpolar residues extends through the remainder of the Pep M5 molecule, with some discontinuities and irregularities. The molecule contains two distinct regions that differ in the pattern of distribution of the nonpolar and charged residues. The 7-residue pattern "a, b, c, d, e, f, g" in region 13-121 is atypical in that position "a" is predominantly occupied by asparagine, rather than nonpolar residues. On the other hand, the periodicity in region 122-196 is more typical of that found in other coiled-coil proteins, such as the myosin rod region, keratin, desmin, and vimentin, rather than tropomyosin. Although the periodicity in nonpolar residues is not highly regular, the predominance of basic and acidic residues in the inner "e" and "g" positions, respectively, suggests that ionic interactions between chains may contribute significantly to the stability of the coiled-coil. The distribution of charged residues in the outer positions within the two regions of the molecule is also distinct. The NH2-terminal region carries a significantly higher net negative charge than the COOH-terminal region, suggesting that the former region may play an important role in some of the biological functions of the Pep M5 molecule.